Pemahaman Aktual mengenai Keselamatan di Luar Gereja dalam Konteks Pluralisme - Pangestu, Yanuarius Murdi; Subali, Yohanes; Yudha Putranto, Leonardus Andhika (Forum, 2025)
The understanding of salvation outside the Church becomes a relevant discussion, especially when people encounter the reality of a pluralistic society. This research aims to explore the understanding of the people in nine parishes of Purwokerto Diocese about the possibility of salvation outside the Church. The selection of the people in Purwokerto Diocese as the research subject is based on the peculiarity of the Church context there as a small group in the midst of a predominantly Muslim society. The method used was quantitative data collection through the completion of a digital questionnaire. The data obtained was processed using the gap analysis method. The inclusive attitude of believers towards salvation outside the Church aligns with the spirit of the Second Vatican Council. This is influenced by the plausibility factor where the more plural the world is, the more plausibility structures are believed. This factor softens the interpretation of Extra Ecclesiam Nulla Salus. This inclusive attitude is an encouragement of the Church's mission to embrace everyone as exemplified by Pope Francis.